TO STUDY THE CONTRIBUTION OF EASTERN SCIENTISTS TO WORLD CIVILIZATION (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This article illustrates the use of scientific legacies of Central Asian scientists in the natural sciences in teaching physics is widely used in Central Asia since ancient times in the field of physics, astronomy, mathematics, medicine, chemistry, textile and architecture.